Mitochondrial production of reactive oxygen species 1 - Brand, Martin (Henry Stewart Talks, 2018)
The reduction of oxygen and production of reactive oxygen species (ROS), Twelve sites of ROS production in mitochondria, Measurement of specific sites in mitochondria, Capacity of each site in optimised conditions, Capacities versus native rates, Contribution of each site under native conditions with conventional/physiological substrates